Growth and reproduction performances of earthworm (Perionyx excavatus) fed with different organic waste materials - Sadia, Masuma Akter; Hossain, Md Amzad; Islam, Md Rabiul; Akter, Taslima; Shaha, Dinesh Chandra (Journal of Advanced Veterinary and Animal Research, 2020)
Objective: The purpose of the experiment was to examine the effect of different food sources on the growth and reproduction performances of an epigeic earthworm Perionyxexcavatus. Materials and Methods: The experiment was carried out in 18 cylindrical plastic containers for 10 weeks. The study was designed with six treatments, each having three replicates. In control treatment (T1), cow dung was used as the only food source for the earthworm. In another five treatments, water hyacinth (T2), chopped banana plant trunk (T3), vegetable scrap (T4), paddy straw (T5), and sugarcane bagasse (T6) were used as food sources with cow dung as bedding material. Results: The maximum weight gain of earthworm P. excavatuswas 3,294.7 ± 4.5 mg for the food staff of vegetable scrap (T4). Earthworm P. excavatusfed with chopped banana plant trunk (T3) showed a very similar weight gain of 3,243.7 ± 3.8 mg. On the contrary, the minimum weight gain was 1,799.7 ± 3.5 mg for the food staff of paddy straw (T5). The maximum cocoon number of 137.33 ± 6.46 mg was observed in T3, whereas a minimum number of 36.67 ± 4.16 mg in T1. The highest number of hatchlings (12.33 ± 0.88 mg) was recorded in treatment T3, whereas the least number of hatchling (5.00 ± 0.58 mg) was observed in T1. Conclusion: It was concluded that, among the six different food sources, chopped banana plant trunk was preferable food source to the earthworm for growth and reproduction. Adv. Vet. Anim. Res., 7(2): 331-337, June 2020